Abyss of despair : the famous 17th century chronicle depicting Jewish life in Russia and Poland during the Chmielnicki massacres of 1648-1649 = Yeven metzulah /: the famous 17th century chronicle depicting Jewish life in Russia and Poland during the Chmielnicki massacres of 1648-1649 = Yeven metzulah. (2018) - Unknown
No abstract available